Trends in central bank independence: A de-jure perspective - Davide Romelli (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2024)
This paper presents an extensive update to the Central Bank Independence - Extended (CBIE) index, originally developed in Romelli (2022), extending its coverage for 155 countries from 1923 to 2023. The update reveals a continued global trend towards enhancing central bank independence, which holds across countries' income levels and indices of central bank independence. Despite the challenges which followed the 2008 Global financial crisis and the recent re-emergence of political scrutiny on central banks following the COVID-19 pandemic, this paper finds no halt in the momentum of central bank reforms. I document a total of 370 reforms in central bank design from 1923 to 2023 and provide evidence of a resurgence in the commitment to central bank independence since 2016. These findings suggest that the slowdown in reforms witnessed post-2008 was a temporary phase, and that, despite increasing political pressures on central banks, central bank independence is still considered a cornerstone for effective economic policy-making.
Keywords: E58; G28; N20; 330; Central banking; central bank independence; central bank governance; legislative reforms